NASIONALISME DAN INTEGRASI INDONESIA: NASIONALISME PANCASILA - Falah, Fajrul; Muhyidin (The Republic : Journal of Constitutional Law, 2024)
Of course, all the people of this nation do not want to be said to be a "hypocrite", namely a person who denies existing values envisioned, formulated and enforced by our predecessors. In this case, Gaining independence and upholding national dignity are ideal swhich was fought for by the founders of this nation. However, what happened it seems that the ideals that had been realized have now been denied. Some in among us have become "hypocrites", so that our self-esteem as a nation seems to have disappeared and is even happy to be that nation "unjusted and colonized". In order to criticize current behavior seems off the mark, this article will invite all components to take a look go back to history, so you can see how noble the struggle of the people was the founders of this nation because they have upheld noble values seems to be reflected in Pancasila. Likewise, looking at history will visible, it is true that the spirit of nationalism has been embedded in the person as Indonesian people, or it turns out we are just hypocrites. In fact, many components of this nation have denied the values ​​of Pancasila, so it is difficult to be said to be a group with a soul nationalism. Why not, don't some people already attach importance? himself, for example, by carrying out corrupt practices or doing whatever even in order to obtain what he wants, for example power. As well as, It turns out that this nation's government doesn't have the power, so they let it go and even give other nations the opportunity to bully and oppress. It is clear that colonialism in its physical form has disappeared from this nation, of course but isn't neocolonialism already growing which is actually more painful, because it seems as if this nation has been tormented for a long time and did not immediately find healing. Keywords: Hypocrisy, nationalism, neocolonialism, corruption, Pancasila, and history.